Critical analysis of the inadequacies of the peaceful assembly act / Nur Shazlin Muhamad Asri … [et al.] - Muhamad Asri, Nur Shazlin; Mohd Malian, Ain Najwa; Aaron Anthony, Terence; Mohd Haris, Nurul Atikah (Faculty of Law, 2014)
This paper studies the inadequacy of the newly implemented PAA which allows the Malaysian citizen to have the assembly on certain matter that arises. To extract the relevant information, semi-structured interviews were conducted with police officer, the lecturers and people in judiciary field to supplement the library-based information which were mostly on article of another country that we compared mainly being United Kingdom and Australia who had the same law implemented. Factors that we considered are like how the law will assist the society, the inadequacy of the law in governing the maturity of the citizens, and improvement that should be taken from time to time. Our study also signify that although it is too soon to study whether this newly legislated law will be able to facilitates our citizens needed, worldwide statistics have proven this fact. Finally, our findings indicate that although the government bodies are certain that enough research has been done before implementing the law, there are still lacuna in dealing with the society and their own hidden agendas and that's why this law should be more complete and critical. Lastly, the end-result will largely depend on public's acceptance and the authority to enforce the law justly.